FACTORS ASSOCIATED WITH THE NUTRITIONAL STATUS OF TODDLERS IN TETEHOSI AFIA VILLAGE, GUNUNG SITOLI UTARA SUB-DISTRICT IN 2023 - Lomboe, Fanny Grace (Akupun Tour Publisher, 2023)
Background: Under-five nutrition is influenced by socio-economic factors and socio-cultural backgrounds related to diet and nutrition. Inadequate nutrition in the first five years of life results in irreversible impairment of physical, mental, and brain growth and development. The measure of success in nutritional fulfillment is nutritional status. The nutritional status of children under five reflects the level of development and welfare of society in a country and is related to the future health status of children. Purpose: The purpose of this study is to determine the factors associated with the nutritional status of toddlers of farming families in Tetehosi Afia Village, North Gunungsitoli District, in 2023. Method: The type of research used in this study is quantitative with a cross-sectional design. The population in this study was all mothers who had toddlers in Tetehosi Afia Village, the work area of the UPTD Puskesmas of North Gunungsitoli District, Gunungsitoli City, which amounted to 169 toddlers. The sample technique used was proportional random sampling, totaling 55 samples. The research analysis used the chi-square test through cross-tabulation with α <0.05. Statistical analysis revealed that respondents' education (p-value 0.000), occupation (p- value 0.002), income (p-value 0.036), and knowledge (p-value 0.000) have a relationship with the nutritional status of toddlers in Tetehosi Afia Village, Gunungsitoli Utara District and for family size (p-value 0.785), there is not relationship with the nutritional status of toddlers in Tetehosi Afia Village, Gunungsitoli Utara District. Disscusion and Conclusion: It is recommended for health workers to conduct nutrition counseling for infants and toddlers with mothers according to the level of education and knowledge of the mother and the age of the child.